Informative role of crime scene for the nomination versions in the investigation of environmental crimes (Journal of actual problems of jurisprudence, 2018)
Possibilities of inspection of the scene in establishment of circumstances of incident are shown in article. Authors opened essence of search work of the investigator which has to consist not only in finding of material traces. As thought process by definition of communication of elements of a material situation of a crime with the occurred event is important as it has to be carried out at survey, an imagination role, etc. is presented in this article.Key words: Inspection of the scene, proof, tactics, direct perception, search, analysis, reconstruction, relevancy of traces.